Otentisitas Hadis-Hadis dalam Majalah Keislaman di Minangkabau Awal Abad ke-20 - Yasti, Suci Amalia; Rafika, Alfiah; Saputra, Doni; Wendry, Novizal (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The mass media contained actual issues of the day and also contained hadith. Then in the context of Minangkabau in the 20th century, the use of hadith was used as a means of legitimizing the author to strengthen his ideas. Among the mass media in print that was published was Al-Itqan Magazine. This article aims to determine the quality of the hadith used in the magazine. The author used a qualitative method focusing on the hadith documents contained in Al-Itqan magazine published on March 19, 1923 which contained 4 traditions. The hadith were interpreted using the rules of hadith validity which include the continuity of the sanad, fairness, perfecthabitat, absence of shaz and illat. The study found that the hadith contained in the magazine contained only the matan. After locating them in the books of hadith, 19 hadith from various sanads and narrators were found. Then from these 19 traditions, there are three traditions that are directly assessed by hadith scholars about the quality of the hadith, namely the hadith line narrated by Muhammad al-Dinuriy al-Qadhi al-Makiy that the hadith has an isnad that is Dhaif Jiddan, then in the narration of Imam Ahmad bin Hanbal that the hadith is sahih, and finally in the narration of Al-Hakim Al-Naisaburi that the hadith is sahih.